ホッキョクケン コウクウキ カンソク (AAMP98) ニ オケル タイキ エアロゾル リュウシ ノ チョクセツ サイシュウ - 原, 圭一郎; ハラ, ケイイチロウ; 岩坂, 泰信; イワサカ, ヤスノブ; 猪股, 弥生; イノマタ, ヤヨイ; 長田, 和雄; オサダ, カズオ; 松永, 捷司; マツナガ, カツジ; 山形, 定; ヤマガタ, サダム; et al. (国立極地研究所, 2002)
P(論文) 春季北極大気中の大気エアロゾル粒子の性状を知るために， AAMP98において境界層内～成層圏下部にかけて，大気エアロゾル粒子の直接採集を行った．捕集されたエアロゾル粒子は，走査型電子顕微鏡—エネルギ一分散型X線分析装置により，形態観察と組成分析を行った．対流圏～成層圏下部の全体の空間では，硫酸と見られるSを含む粒子が多数を占めていた．また，土壌・ ダスト粒子と考えられる不定形粒子，海塩粒子のような結晶質の粒子は境界層内～約7000 mに確認された． In order to know the morphology and mixing state of atmospheric aerosol particles in the spring Arctic atmosphere, direct sampling of aerosol particles was carried out using an aerosol impactor system during the Arctic Airborne Measurement Program (AAMP 98). Aerosol samples were observed with a scanning electron microscope and analyzed with an energy-dispersive X-ray spectrometer. Aerosol particles with clear satellite structure due to sulfuric acid droplets were observed in samples collected in the lower stratosphere and free troposphere. On the other hands, aerosol particles with crystal and satellite structure due to droplets of sea salt particles were observed in the boundary layer. departmental bulletin paper